Structure and Optical Property of Gold Nanoparticles Synthesized by Modified Polyol Method - Long, Nguyen Viet (Communications in Physics, 2021)
In this research, Au nanoparticles were successfully synthesized by modified polyol method with commercial precursors to be gold (III) chloride trihydrate (HAuCl4·3H2O), ethylene glycol (EG), poly(vinylpyrrolidone) (PVP), sodium borohydride (NaBH4). The structure and properties of as-prepared Au nanoparticles have been investigated by X ray diffraction (XRD), transmission electron microscopy (TEM), and UV-vis-NIR spectroscopy. As a result, Au nanoparticles with the average particle size of 28.80 nm were successfully synthesized in the range of about 50 nm. It is evidenced that the assembly of gold nanoparticles was presented in their nucleation, growth, and formation.